The inter-rater reliability of the diagnosis of surgical site infection in the context of a clinical trial. Issue 8 (August 2016) - Nuttall, J.; Evaniew, N.; Thornley, P.; Griffin, A.; Deheshi, B.; O'Shea, T.; Wunder, J.; Ferguson, P.; Randall, R. L.; Turcotte, R.; Schneider, P.; McKay, P.; et al.
Abstract : Objectives: The diagnosis of surgical site infection following endoprosthetic reconstruction for bone tumours is frequently a subjective diagnosis. Large clinical trials use blinded Central Adjudication Committees (CACs) to minimise the variability and bias associated with assessing a clinical outcome. The aim of this study was to determine the level of inter-rater and intra-rater agreement in the diagnosis of surgical site infection in the context of a clinical trial. Materials and Methods: The Prophylactic Antibiotic Regimens in Tumour Surgery (PARITY) trial CAC adjudicated 29 non-PARITY cases of lower extremity endoprosthetic reconstruction. The CAC members classified each case according to the Centers for Disease Control (CDC) criteria for surgical site infection (superficial, deep, or organ space). Combinatorial analysis was used to calculate the smallest CAC panel size required to maximise agreement. A final meeting was held to establish a consensus. Results: Full or near consensus was reached in 20 of the 29 cases. The Fleiss kappa value was calculated as 0.44 (95% confidence interval (CI) 0.35 to 0.53), or moderate agreement. The greatest statistical agreement was observed in the outcome of no infection, 0.61 (95% CI 0.49 to 0.72, substantial agreement). Panelists reached a full consensus in 12 of 29 cases and near consensus in five of 29 cases when CDC criteria were used (superficial, deep or organ space). A stable maximum Fleiss kappa of 0.46 (95% CI 0.50 to 0.35) at CAC sizes greater than three members was obtained. Conclusions: There is substantial agreement among the members of the PARITY CAC regarding the presence or absence of surgical site infection. Agreement on the level of infection, however, is more challenging. Additional clinical information routinely collected by the prospective PARITY trial may improve the discriminatory capacity of the CAC in the parent study for the diagnosis of infection. Cite this article: J. Nuttall, N. Evaniew, P. Thornley, A. Griffin, B. Deheshi, T. O'Shea, J. Wunder, P. Ferguson, R. L. Randall, R. Turcotte, P. Schneider, P. McKay, M. Bhandari, M. Ghert. The inter-rater reliability of the diagnosis of surgical site infection in the context of a clinical trial. Bone Joint Res 2016;5:347–352. DOI: 10.1302/2046-3758.58.BJR-2016-0036.R1.